2016
DOI: 10.1016/j.jmmm.2016.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and transport properties of single crystalline RPd2P2 (R=Y, La–Nd, Sm–Ho, Yb)

Abstract: Single crystals of RPd2P2 (R=Y, La-Nd, Sm-Ho, Yb) were grown out of a high temperature solution rich in Pd and P and characterized by room-temperature powder X-ray diffraction, anisotropic temperature-and field-dependent magnetization and temperature-dependent in-plane resistivity measurements. In this series, YPd2P2 and LaPd2P2 and YbPd2P2 (with Yb +2 ) are non localmoment bearing, whereas CePd2P2 and PrPd2P2 order at low temperature with a ferromagnetic component along the crystallographic c-axis. The rest o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…These papers also confirmed ferromagnetic order in CePd 2 P 2 below about 28.4 K. Neutron diffraction and DC magnetization measurements were performed by Ikeda et al [19] on a polycrystalline sample, including a magnetically aligned polycrystalline sample, which revealed the magnetic anisotropy of CePd 2 P 2 , with the c-axis as the magnetic easy axis. This is confirmed by single crystal work [20]. The compound CeNi 2 P 2 shares the ThCr 2 Si 2 crystal structure with CePd 2 P 2 , but exhibits a non-magnetic ground state [21], suggesting Pdto-Ni substitution can drive a transition from magnetic to non-magnetic.…”
Section: Introductionmentioning
confidence: 75%
“…These papers also confirmed ferromagnetic order in CePd 2 P 2 below about 28.4 K. Neutron diffraction and DC magnetization measurements were performed by Ikeda et al [19] on a polycrystalline sample, including a magnetically aligned polycrystalline sample, which revealed the magnetic anisotropy of CePd 2 P 2 , with the c-axis as the magnetic easy axis. This is confirmed by single crystal work [20]. The compound CeNi 2 P 2 shares the ThCr 2 Si 2 crystal structure with CePd 2 P 2 , but exhibits a non-magnetic ground state [21], suggesting Pdto-Ni substitution can drive a transition from magnetic to non-magnetic.…”
Section: Introductionmentioning
confidence: 75%
“…Following this observation, we previously demonstrated that low‐melting metal‐sulfur mixtures could serve as powerful solvents for growing a variety of binary and ternary sulfide materials [10] . More recently, we used transition metal‐phosphorous melts to grow Fe 5 B 2 P, ZrMnP, HfMnP and RPd 2 P 2 out of TM‐P‐X self‐fluxes [27–29] …”
Section: Introductionmentioning
confidence: 85%
“…Фосфіди складу RPd 2 P 2 , де R = Eu-Dy, мають парамагнітні властивості. Також відомо, що для сполуки CePd 2 P 2 властивий Кондо-ефект [19], а за низьких температур наявні феромагнітні впорядкування [20][21][22][23][24][25].…”
Section: вступunclassified